Citation Indexes Accounting for Authorship Order in Coauthored Research—Review and New Proposal. Issue 4 (1st October 2016) - Abambres, Miguel; Arab, Paola
ABSTRACT: Research articles' authorship confers credit and has important academic, social, and financial implications. After a paper is published, credit is harvested via citations. Currently, authorship order is not taken into account by the bibliometric citation indexes used in citation databases. It means that one gets the same measure of credit for a single- or first-authored article as for a multiauthored publication in which one is a middle author among other coauthors. This reality may not be appropriate, and it does matter since (1) it influences scientific performance assessment, which is extremely important at the time of recruitment or allocation of grants; and (2) it may affect scientific legacy. This work aims at recalling for the scientific community the need of change of the actual assessment paradigm by providing a review of the main bibliometric index and authorship credit models proposed in the literature as well as an original scientific performance evaluation method suggested by the authors.